2021
DOI: 10.3389/fphar.2021.700217
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum ZS40 Ameliorates Inflammation in Mice With Ulcerative Colitis Induced by Dextran Sulfate Sodium

Abstract: Ulcerative colitis is an inflammatory disease of the intestine caused by many reasons, and it may even develop into colon cancer. Probiotics are normal bacteria that exist in the human body and have been proven to regulate the balance of intestinal flora and alleviate inflammation. The current study aimed to study the effect of Lactobacillus fermentum ZS40 (ZS40) on dextran sulfate sodium (DSS)-induced ulcerative colitis mice. The length and weight of the colon were measured, and the histopathological morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…57 The administration of water kefir microbiota effectively decreased the expression of TLR4, MyD88, and NF-κB, which was similar to previous studies which have shown that Lactobacillus, Saccharomyces, and Bifidobacterium can relieve colitis by decreasing the expression of TLR4, MyD88, and NF-κB. [58][59][60] These findings…”
Section: Papersupporting
confidence: 87%
“…57 The administration of water kefir microbiota effectively decreased the expression of TLR4, MyD88, and NF-κB, which was similar to previous studies which have shown that Lactobacillus, Saccharomyces, and Bifidobacterium can relieve colitis by decreasing the expression of TLR4, MyD88, and NF-κB. [58][59][60] These findings…”
Section: Papersupporting
confidence: 87%
“…39 In addition, L. fermentum can down-regulate the level of inflammatory cytokines and up-regulate the level of anti-inflammatory cytokines in mice challenged with dextran sulfate sodium. 40 In this study, we found that both LF23 and LG80 significantly reduced the levels of inflammatory cytokine TNF-α, IL-1β and IL-6.…”
Section: Discussionmentioning
confidence: 50%
“…Probiotics are able to attenuate inflammatory processes in UC by inhibiting the expression and production of pro-inflammatory transcription factors and/or molecules, and/or by inducing immunoregulatory mechanisms such as the differentiation of Th regulatory lymphocytes in the gut mucosa [ 69 ]. Several strains of Limosilactobacillus (formerly Lactobacillus ) fermentum have been shown to mitigate inflammatory processes by inhibiting the expression of pro-inflammatory transcription factors (nuclear factor-κB p65, mitogen-activated protein kinases p38 and JNK1/2) and downregulating the level of pro-inflammatory molecules (inducible nitric oxide synthase, cyclooxygenase 2) and cytokines (IL-6, TNF-α, IL-12) [ 69 , 70 , 71 ]. Other probiotic strains, such as Lactiplantibacillus (formerly Lactobacillus ) plantarum and Bifidobacterium longum , have been documented to alleviate chemically induced colitis by restoring the Th17/Treg balance in the lamina propria of the colon [ 72 ].…”
Section: Conventional Probiotics and Ucmentioning
confidence: 99%